Double-Blind, Randomized Comparison of Systemic Continuous Infusion of 0.25 Versus 0.50 mg/kg/24 h of Alteplase over 3 to 7 Days for Treatment of Deep Venous Thrombosis in Heparinized Patients: Results of the European Thrombolysis with rt-PA in Venous Thrombosis (ETTT) Trial - Bounameaux, H; Banga, J D; Bluhmki, E; Coccheri, S; Fiessinger, J N; Haarmann, W; Lockner, D; Mahler, F; Ninet, J; Schneider, P A; de Torrente, A; van der Meer, J; Verhaeghe, and R (Thrombosis and Haemostasis, 1992)
Thirty-two patients with acute, proximal-vein thrombosis were treated with heparin and alteplase (0.25 versus 0.5 mg/kg/24 h during 3-7 days) in a randomized, double-blind, multicenter, European (ETTT) trial. The treatment resulted in a decrease of the venographic Marder’s score from 18 (6-25) to 13 (2-24) units (median, range) in Group I (0.25 mg/kg/24 h, n = 15, median decrease 3.0, p = 0.32) and from 17.5 (3-33) to 15.5 (0-27) in Group II (0.5 mg/kg/24 h, n = 16, median decrease 4.0, p = 0.23). Comparison of the sequential venograms could be performed in 14 cases of Group I and in 15 cases in Group II. A minority of patients showed substantial partial recanalization of the initially obstructed veins on the control venogram (one in each treatment group) and most of the control venograms showedThus, the results of the ETTT trial show that the used low dosages of alteplase administered intravenously over 3-7 days in heparinized patients cannot be recommended as a treatment for patients with deep venous thrombosis of lower limbs and/or pelvis. Further studies are needed to define a more suitable dosage regimen of alteplase in this indication.